Use of endpoints in phase III randomized controlled trials for acute myeloid leukemia over the last 15 years: a systematic review. Issue 2 (28th January 2023) - Shahzad, Moazzam; Chaudhary, Sibgha Gull; Tariq, Ezza; Mushtaq, Ali Hassan; Anwar, Iqra; Ahmed, Nausheen; Bansal, Rajat; Lutfi, Forat; Balusu, Ramesh; Abdelhakim, Haitham; Yacoub, Abdulraheem; Hematti, Peiman; et al.
Abstract: We systematically evaluated the primary and secondary endpoints used in acute myeloid leukemia (AML) phase III randomized controlled trials (RCTs). We included 238 phase III AML RCTs in the past 15 years that reported 279 primary endpoints and 657 secondary endpoints. Overall survival (OS), progression-free survival (PFS), event-free survival (EFS), and complete remission (CR) were primary endpoints in 120 (43%), 34 (12%), 30 (11%), and 41 (15%) studies, respectively. OS (12.5%), PFS (13.2%), CR (14%), safety (11%), and EFS (9%) were commonly reported secondary endpoints. Among primary endpoints, a higher use of OS (OR 2.03, 95%CI 1.10–3.75, p = 0.023) and lower use of PFS (OR 0.25, 95%CI 0.12–0.52, p < 0.001) was observed from 2014 to 2021 compared to 2006–2013; CR was frequently used in relapsed/refractory compared to frontline RCTs (OR 2.20, 95%CI 1.11–4.38, p = 0.025); EFS was frequently used in frontline compared to relapsed/refractory AML RCTs (OR 10.11, 95%CI 1.34–76.34, p = 0.025). A higher trend in the use of clinically meaningful and objective endpoint of OS over the last 15 years.